2022
DOI: 10.1021/acs.cgd.2c00313
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Solid State Luminescence Properties of Organic Crystals via Solid Solution Formation: The Example of 4-Iodothioxanthone–4-Chlorothioxanthone System

Abstract: Solid solutions with fine-tunable photoluminescence have been obtained in a 4-iodothioxanthone−4-chlorothioxanthone system. Both pure components are room-temperature luminophors demonstrating different luminescence properties. It was discovered that in the 4-chlorothioxanthone structure, up to half of the molecules can be replaced by the iodo analogue obtaining solid solutions in the respective composition range. Despite this solid solution existing in such a large composition range, the variation of the lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…LED and solar cells. 1,2 Recently, crystalline solid solutions of organic compounds have also been encountered as a common retention mechanism for impurities in solution crystallization. In these investigations, 3,4 structurally similar impurities became embedded within individual crystals of the product and could not be easily removed.…”
Section: Introductionmentioning
confidence: 99%
“…LED and solar cells. 1,2 Recently, crystalline solid solutions of organic compounds have also been encountered as a common retention mechanism for impurities in solution crystallization. In these investigations, 3,4 structurally similar impurities became embedded within individual crystals of the product and could not be easily removed.…”
Section: Introductionmentioning
confidence: 99%
“…The weak intermolecular interactions, however, are often weak enough so that their alteration will not exclusively prevent the formation of solid solutions but important enough to determine the replacement possibilities . Nevertheless, it is reported that solid solutions between similar molecules can be obtained if the exchanged atoms or groups are not involved in energetically notable directional or electrostatic interactions. , Overall, the studies of whether the replacement of relatively similar functional groups of organic molecules would allow the formation of either isostructural phases or solid solutions have gained increasing attention as a tool to develop or test the rules of crystal engineering. , Moreover, solid solutions can be used to modify and fine-tune various properties of crystals, , including solubility, , optical properties, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Matters become more involved when the investigator embarks on a systematic study of higher cocrystals, namely, those that contain three or more distinct molecular components. Crystals with more than two molecular components are of interest, in that there is a question as to whether an increase in the number of components leads to further modularity in crystal properties leading to polyfunctional materials. As in binary systems, higher cocrystal formation is enabled by mutual recognition of chemical and geometrical features in the constituent molecules through critical properties of the relevant supramolecular synthons. , The first development in the direction of higher order cocrystals was executed by the Aakeröy group, where they designed a ternary cocrystal based on a graded interaction hierarchy . The best donor establishes a hydrogen bond with the best acceptor, while the second best donor prefers to bind with the second best acceptor to give hydrogen-bonded ternary cocrystals .…”
Section: Introductionmentioning
confidence: 99%